Malaysia and forced migration - Idris, Arzura (Intellectual discourse, 2012)
This paper analyzes the phenomenon of "forced migration" in Malaysia. It examines the nature of forced migration, the challenges faced by Malaysia, the policy responses and their impact on the country and upon the forced migrants. It considers forced migration as an event hosting multifaceted issues related and relevant to forced migrants and suggests that Malaysia has been preoccupied with the issue of forced migration movements. This is largely seen in various responses invoked from Malaysia due to "south-south forced migration movements." These responses are, however, inadequate in terms of commitment to the international refugee regime. While Malaysia did respond to economic and migration challenges, the paper asserts that such efforts are futile if she ignores issues critical to forced migrants.